Knowledge Mapping of Olfactory Dysfunction: A Bibliometric Study - Hu, Wen; Chen, Na; Yan, Weiheng; Pei, Pei; Wei, Yongxiang; Zhan, Xiaojun (Frontiers in Systems Neuroscience, 2022)
Background Olfaction is one of the five basic senses of human beings. As such, olfactory dysfunction seriously affects patients' quality of life and can even endanger them. In recent years, olfactory dysfunction has attracted greater research interest, and numerous studies have been published on olfactory dysfunction. However, there are few studies on olfactory dysfunction through bibliometric analysis. This study aims to describe the current situation and identify the foci and potential new research directions of olfactory dysfunction using a bibliometric approach. Methods Articles related to olfactory dysfunction published from 2002 to 2021 were located in the Web of Science Core Collection of Clarivate Analytics (London, UK). Bibliometric analyses were conducted with the CiteSpace (Chaomei Chen, Drexel University, Philadelphia, PA, USA) and VOSviewer (Center for Science and Technology Studies, Leiden University, Leiden, Netherlands) software programs. Results The number of articles published each year showed an upward trend, especially in 2020, where a sharp increase had occurred due to the coronavirus disease 2019 (COVID-19) pandemic. The United States was the country with the most publications and the strongest international cooperation. In terms of institutions, the greatest number of publications from a single institution came from Dresden University of Technology. Thomas Hummel was the author who had contributed the most articles. An analysis of co-citation networks and burst keywords in the field revealed a shift from “gonadotropin-releasing hormone” and “apoptosis” earlier on to “olfactory training,” “COVID-19,” and “Parkinson's disease” more recently. “Outcome,” “COVID-19,” “infection,” and “pathogenesis” are topics of the research frontier and hotspots. Conclusion More attention has been paid to olfactory dysfunction as the understanding of it has improved in the past 20 years. This study provides researchers with an objective, systematic, and comprehensive analysis of the literature on olfactory dysfunction. The current frontier areas and hotspots in the field focus on the pathological mechanisms of olfactory dysfunction after infection with COVID-19 and its different prognoses. The pathophysiological mechanism of olfactory dysfunction in neurodegenerative diseases and COVID-19 will be a primary future research direction.